Acute effects of technical instructions on sprint acceleration technique and performance - Bezodis, N. E.; North, J. S.; Razavet, J. L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study investigated the acute effect of verbal technical instructions intended to alter attentional focus during a 10 m sprint. Team sports athletes (n = 15) completed maximal effort sprints under a control condition and two experimental conditions: internal and external focus. Lower-body kinematic and external kinetic data were collected near the 5 m mark. Total sprint time was longer in both experimental conditions than the control condition (p < 0.05). Both experimental conditions altered ankle and knee angles at touchdown and led to more vertically oriented ground reaction forces (all p < 0.05). Whilst these instructions were detrimental to performance, the results support the importance of technical ability for sprint acceleration. Future studies should seek to identify instructions, potentially used within training programmes, which could be beneficial to performance.